2018
DOI: 10.1038/s41375-018-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of pre-leukemic clones during first remission and risk of relapse in acute myeloid leukemia

Abstract: Some patients with acute myeloid leukemia (AML) who are in complete remission after induction chemotherapy harbor persisting pre-leukemic clones, carrying a subset of leukemia-associated somatic mutations. There is conflicting evidence on the prognostic relevance of these clones for AML relapse. Here, we characterized paired pre-treatment and remission samples from 126 AML patients for mutations in 68 leukemia-associated genes. Fifty patients (40%) retained ≥1 mutation during remission at a VAF of ≥2%. Mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 35 publications
8
95
3
1
Order By: Relevance
“…The general persistence of mutations in remission was associated with worse prognosis in our study, irrespective of VAFs or the number of mutations, which is in agreement with previous reports (Jongen‐Lavrencic et al , ; Rothenberg‐Thurley et al , ). Although DNMT3A mutations are the most frequently persisting mutations in AML, we and others have showed that their persistence does not seem to further impact prognosis of the DNMT3A mutated patients (Gaidzik et al , ; Jongen‐Lavrencic et al , ; Sun et al , ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The general persistence of mutations in remission was associated with worse prognosis in our study, irrespective of VAFs or the number of mutations, which is in agreement with previous reports (Jongen‐Lavrencic et al , ; Rothenberg‐Thurley et al , ). Although DNMT3A mutations are the most frequently persisting mutations in AML, we and others have showed that their persistence does not seem to further impact prognosis of the DNMT3A mutated patients (Gaidzik et al , ; Jongen‐Lavrencic et al , ; Sun et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…While previous studies identified persistent mutations in AML remission in 40–52% patients, we identified persistent mutations in a lower fraction of patients (33%), despite an identical spectrum of affected genes ( DNMT3A, TET2, IDH1/2, RUNX1, ASXL1, and SRSF2 ) and identical detection thresholds (2% VAF) (Klco et al , ; Morita et al , ; Rothenberg‐Thurley et al , ). This lower proportion of persistent mutations in our cohort is likely explained by the preferential selection of samples from the deepest (molecular) remission while other studies analysed post‐induction samples possibly including residual low‐level leukemic mutations representing minimal residual disease (MRD) (Jongen‐Lavrencic et al , ; Klco et al , ; Rothenberg‐Thurley et al , ). This assumption is supported by Parkin et al who analysed remission samples with a sensitivity as low as 0·002% VAF and confirmed that remission samples harbour a mixture of low‐level VAF mutations representing residual leukaemia clones that reappear at relapse, and high‐level mutations probably representing ancestral pre‐leukemic clones (Parkin et al , ).…”
Section: Discussioncontrasting
confidence: 48%
“…If residual leukemia cells are not able to gain the mutation quickly enough, they may be eradicated by the therapy. Thus, mutation clearance is directly correlated to the risk of AML relapse and its dynamics . On the other hand, as the subclonal diversity of AML at diagnosis is commonly high, individual cells capable of giving rise to relapse may already exist at diagnosis .…”
Section: Summary Discussion Outlookmentioning
confidence: 99%
“…86 In a larger cohort of 126 patients who reached CR after induction chemotherapy, 40% had at least one persisting mutation (VAF >2%) in a CR blood or marrow specimen. 87 In most of these patients, only a subset of the AML-associated mutations remained detectable and had allele frequencies of ≥10%, indicating persistence of preleukemic clones that substantially contributed to remission hematopoiesis, as opposed to a few residual leukemia cells. Patients with persisting mutations were older than those with complete mutation clearance, and mutation persistence was most common in DNMT3A, SRSF2, TET2, and ASXL1, suggesting that at least some of these patients may have had age-associated CH preceding their AML.…”
Section: Persisting Preleukemic Clones In Aml Patients In Remissionmentioning
confidence: 93%